Food Safety Training Is Associated with Improved Knowledge and Behaviours among Foodservice Establishments’ Workers - Hezekiah Kehinde Adesokan; Victor Oluwatoyin Akinseye; Grace Abiodun Adesokan (International Journal of Food Science)
Though several studies have evaluated the association between food safety training and behavior, little has investigated different training components in association with food handlers’ performance. Foodservice workers (N=211) with at least two years’ experience were willing to participate and were selected from major foodservice establishments in Ibadan, southwestern Nigeria, and completed a survey to evaluate the association between training, training area, duration, and refresher training and food safety knowledge and practices. We observed an association between training and knowledge (P=0.000) as well as practices (P=0.05) of food safety while different training areas contributed similarly to food handlers’ knowledge (P=0.17) and practices (P=0.08). However, there was a significant decline in knowledge (P=0.01) and practices (P=0.001) with an increase in training duration. Furthermore, foodservice employees with refresher training demonstrated significantly higher knowledge (P=0.000) and practice (P=0.003) levels than those without, being about 45 and 14 times more likely to, respectively, improve their knowledge (OR = 45; 95% CI: 3.47–584.34) and practice (OR = 13.5; 95% CI: 2.01–90.69). Researchers should always consider varying training components before making assertions regarding effectiveness of training on foodservice workers’ behaviour.